Phenotypic and molecular characterization of Prototheca wickerhamii from a Brazilian case of human systemic protothecosis. - Luciana Duarte-Silva; Raquel Vilela; Isabela A Rodrigues; Vanessa C R Magalhães; Marcelo V Caliari; Leonel Mendoza; Adriana Oliveira Costa (PLoS Neglected Tropical Diseases)
The genus Prototheca (alga) comprises a unique group of achlorophyllic saprotrophic and mammalian pathogen species. Despite its rare occurrence in humans and animals, protothecosis is considered an emerging clinical entity with relevance in immunocompromised patients. In this study, the characterization of spherical structures with endospores recovered from a blood culture in an HIV patient was investigated using phenotypic and molecular methodologies. On 2% Sabouraud dextrose agar, the isolate displayed morphological and biochemical characteristics found on isolates identified as Prototheca wickerhamii. To validate these analyses, molecular phylogeny of the internal transcript space (ITS) partial gene confirmed the identity of the isolate as P. wickerhamii. This is the first case of systemic human protothecosis in Brazil. The present case of human Prototheca and those reported in the medical literature highlight the need for novel methodologies to identify pathogenic algae in the clinical laboratory, improving in this way the diagnosis and treatment of this group of neglected pathogens.